Post-Rehabilitation Dynamics of Mangrove Vegetation in Tarakan, North Kalimantan - Wiharyanto, Dhimas; Ilman, Muhamad; Salim, Gazali; Hidayat, Wahyu; Ransangan, Julian; Arief, Mochamad Candra Wirawan; Zahidah, Zahidah; Rahman, Abdur; Mujiyanto, Mujiyanto (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
This research examined the post-rehabilitation dynamics of the mangrove ecosystem in the Mangrove and Crab Conservation Area, Tarakan, North Kalimantan, four years after the launch of a community-based restoration program in 2019. The objectives were to evaluate species composition, vegetation structure, and the survival of mangrove seedlings within rehabilitated plots. The sampling was done on purpose in areas that show the main ecological features of the site. This study found five types of mangrove trees: Avicennia alba, Rhizophora mucronata, Avicennia marina, Sonneratia alba, and Xylocarpus granatum. It is fewer than the ten species that were there in the past. Among these, Avicennia alba consistently dominated both the mature and seedling stages, recording the highest relative density (72.56%), frequency (42.86%), and canopy cover (78.08%). Its naturally regenerating seedlings reached a survival rate of 52%, substantially higher than the 17% recorded for planted Rhizophora mucronata. The Avicennia alba is particularly well adapted to the prevailing site conditions, mainly owing to its tolerance of sediment disturbance and variable salinity. This outcome highlights the importance of Assisted Natural Regeneration (ANR) that employs locally adapted species, offering a more practical, cost-effective, and sustainable approach than conventional planting methods. Although there have been some improvements, the decrease in species numbers shows the ecosystem is still in the early stages of recovery. To make sure it stays healthy and strong for the future, it is important to keep the water flowing properly, reduce human impact, and keep up with regular checks and monitoring.